PROFIL LITERASI SAINS PESERTA DIDIK DI SMAN 8 TASIKMALAYA PADA MATERI PERUBAHAN LINGKUNGAN - Fauziah, Nur; Surahman, Endang; Mustofa, Romy Faisal (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This study aims to determine the profile of students' science literacy skills on environmental change material at SMA Negeri 8 Tasikmalaya. This research uses quantitative descriptive method. The population of this study was all X grade SMA Negeri 8 Tasikmalaya which amounted to 12 classes. The sampling technique used purposive sampling with a total sample of 2 classes consisting of 72 students. Science literacy skills used are based on indicators developed by Gormally. The results of research in the field show that in the sub-indicators of science literacy (1) understanding valid scientific arguments obtained a score of 53.88 included in the deficient category, (2) evaluation of validity sources obtained a score of 57.2. (3) evaluating the use and misuse of scientific information obtained a score of 40.8, including into the category of less, (4) understanding the elements of research villages and how they impact scientific findings / conclusions obtained a score of 46.8 including into the category of less, (5) making graphical representations of data obtained a score of 49.3 including into the category of less, (6) reading and interpreting graphical representations of data obtained a score of 54, (7) solving problems using quantitative skills, including probability and statistics obtained a score of 48.61 including into the deficient category, (8) understanding and interpreting basic statistics obtained a score of 53.47 including into the deficient category, (9) justifying conclusions, predictions and conclusions based on quantitative data obtained a score of 52.7 including into the deficient category. To improve students' science literacy skills, it is necessary to use an effective learning model. One of the models that can be used is problem-based learning based on socio-scientific issues. ABSTRAKPenelitian ini bertujuan untuk mengetahui profil kemampuan literasi sains peserta didik pada materi perubahan lingkungan di SMA Negeri 8 Tasikmalaya. Penelitian ini menggunakan metode deskriptif kuantitatif. Populasi penelitian ini adalah seluruh kelas X SMA Negeri 8 Tasikmalaya yang berjumlah 12 kelas. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah sampel sebanyak 2 kelas yang terdiri dari 72 orang peserta didik. Kemampuan literasi sains yang digunakan berdasarkan indikator yang dikembangkan oleh Gormally. Hasil penelitian di lapangan menunjukkan bahwa pada sub indikator literasi sains  (1) memahami argumen ilmiah yang valid memperoleh skor 53,88 termasuk ke dalam kategori kurang, (2) evaluasi sumber validitas memperoleh skor 57,2. termasuk ke dalam kategori kurang, (3) mengevaluasi penggunaan dan penyalahgunaan informasi ilmiah memperoleh skor 40,8, termasuk ke dalam kategori kurang, (4) memahami unsur-unsur desaun penelitian dan bagaimana dampaknya terhadap temuan/kesimpulan ilmiah memperoleh skor 46,8 termasuk ke dalam kategori kurang, (5) membuat representasi grafis dari data memperoleh skor 49,3 termasuk ke dalam kategori kurang, (6) membaca dan menafsirkan representasi grafis dari data memperoleh skor 54,1 termasuk ke dalam kategori kurang, (7) memecahkan masalah dengan menggunakan keterampilan kuantitatif, termasuk probabilitas dan statistik memperoleh skor 48,61 termasuk ke dalam kategori kurang, (8) memahami dan menginterpretasikan statistik dasar memperoleh skor 53,47 termasuk ke dalam kategori kurang, (9) Membenarkan kesimpulan, prediksi dan kesimpulan berdasarkan data kuantitatif memperoleh skor 52,7 termasuk ke dalam kategori kurang. Untuk meningkatkan kemampuan literasi sains peserta didik, di perlukan penggunaan model pembelajaran yang efektif. Salah satu model yang dapat di gunakan adalah problem based learning berbasis socio-scientific issue.